Redescription of the holotype of Finlaya lepchana Barraud, 1923 (Diptera: Culicidae: Aedini) - Reinert, John F. (Zootaxa, 2008)
Barraud (1923a) provided the original description of Finlaya lepchana and based it on the holotype male and two other males from India, Tindharia, Darjeeling Hills, which were reared from larvae collected from bamboo stumps in October 1922. The description is brief and lacks many morphological details. Therefore, the holotype male, deposited in the Natural History Museum (NHM), London, United Kingdom, is redescribed below. The specimen is mounted on a minuten pin extending more or less vertically through the thorax between the mesal margins of the upper proepisterna and exiting the scutum anterior to the prescutellar area. The lower part of the minuten pin is inserted in a rectangular, yellow, plastic stage which is attached near its margin to an insect pin. Four labels are attached to the insect pin and include the following information: Finlaya lepchana Barr., % TYPE (handwritten in black ink except TYPE is typed on a red, paper, triangular label); terminalia ON SLIDE (hand printed in black ink on a white, paper, rectangular label); India: Tindaria, Darjiling Hills, IX.1922, bamboos, Capt. P.J. Barraud, B.M. 1923-207 (partially handwritten and remainder typed in black ink on a white, paper, rectangular label); HOLO- TYPE (printed in black ink on a small, circular, white, paper label with red border). The male genitalia, previously mounted on a microscope slide, have two labels as follow: AЁDES (FINLAYA) LEPCHANA Barr., INDIA, TINDHARIA, DARJEELING Dist., x.1922, from Bamboos, Coll. P. J. BARRAUD, B.M. 1923-207 (hand printed in black ink on a rectangular, brown paper label attached to the left side of the slide); HOLO- TYPE (label printed on a small, circular, white paper label with red border attached to the left side of the slide). The genitalia are mounted beneath a square cover slip and five psocids are embedded in the mounting medium on the margin of the cover slip. The spelling of “Tindaria” and “Darjiling” on the adult label differs from that reported by Barraud (1923a).